2010
DOI: 10.3354/meps08876
|View full text |Cite
|
Sign up to set email alerts
|

Prey dominance shapes trophic structure of the northern California Current pelagic food web: evidence from stable isotopes and diet analysis

Abstract: Eastern boundary current (EBC) upwelling zones are among the most productive of marine ecosystems globally and have been generalized in terms of their food web structure. Little empirically based evidence exists to suggest that there is any one form of trophic control of EBC systems and, because of logistical constraints, knowledge of food web structure is limited in these large marine ecosystems. To determine principal trophic links within the pelagic food web, we combined stable isotope and diet analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
50
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 57 publications
9
50
3
2
Order By: Relevance
“…The fish data from the Bay of Biscay in the northeast Atlantic showed signals from coastal, oceanic and deep-sea areas, where river discharges appeared to be the primary factor in terms of influencing the δ Our study indicated that fish and squids function as the tertiary (TL4) and quaternary (TL5) consumers. Miller et al (2010) found 5 TLs (including sea lion species) in the Northern California Current pelagic food web, where fish had values ranging from 2.7 to 3.8, which were lower than our results. Ranges lower than our observations were also registered in a tropical estuary off the coast of Senegal (2.6−4.7; Faye et al 2011), and for the Bay of Banyuls-sur-Mer (France), where the benthic food web was composed of 4 TLs, with fish distributed between TL3 and TL4 (Carlier et al 2007).…”
Section: Trophic Interactionscontrasting
confidence: 99%
See 3 more Smart Citations
“…The fish data from the Bay of Biscay in the northeast Atlantic showed signals from coastal, oceanic and deep-sea areas, where river discharges appeared to be the primary factor in terms of influencing the δ Our study indicated that fish and squids function as the tertiary (TL4) and quaternary (TL5) consumers. Miller et al (2010) found 5 TLs (including sea lion species) in the Northern California Current pelagic food web, where fish had values ranging from 2.7 to 3.8, which were lower than our results. Ranges lower than our observations were also registered in a tropical estuary off the coast of Senegal (2.6−4.7; Faye et al 2011), and for the Bay of Banyuls-sur-Mer (France), where the benthic food web was composed of 4 TLs, with fish distributed between TL3 and TL4 (Carlier et al 2007).…”
Section: Trophic Interactionscontrasting
confidence: 99%
“…These results suggest mixed diets and TL omnivory. Similar results were reported for pelagic food webs of the California Current upwelling (Miller et al 2010) and the Southern California Current upwelling (Madigan et al 2012).…”
supporting
confidence: 87%
See 2 more Smart Citations
“…Dominant species are the small number of species that significantly affect other species (McNaughton & Wolf, 1970; Whittaker, 1965). Due to their high biomass, large size, high productivity, and other traits (Bouchenak‐Khelladi, Slingsby, Verboom, & Bond, 2014; Collins & Duffy, 2016), they can change environmental conditions and resource availability and thus shape community structure (Frieswyk, Johnston, & Zedler, 2007; Okullo, Greve, & Moe, 2013), community diversity (Kunte, 2008; Okullo et al., 2013), community phylogeny (Chalmandrier, Münkemüller, Lavergne, & Thuiller, 2015), trophic structure (Miller, Brodeur, Rau, & Omori, 2010), and ecosystem functions (Behera et al., 2017; Furey, Tecco, Perez‐Harguindeguy, Giorgis, & Grossi, 2014; Grime, 1998; Mokany, Ash, & Roxburgh, 2008; Seabloom et al., 2015). Both dominant species and keystone species are functionally important, but keystone species are much less abundant (Christianou & Ebenman, 2005; Hurlbert, 1997; Mouquet, Gravel, Massol, & Calcagno, 2013; Power et al., 1996).…”
Section: Introductionmentioning
confidence: 99%